The Correlation of Rapid Antibody Results with SARS-CoV-2 PCR in COVID-19 Patients in Ulin General Hospital Banjarmasin - Isa Ansori; Soraya Riefani; Ira Nurrasyidah (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the cause of clinical disease, better known as COVID-19. The most common method to detect COVID-19 is serological testing of IgM and IgG in response to viral infections using rapid diagnostic test (RDT). Several other guidelines consider polymerase chain reaction (PCR) as the gold standard for diagnosis becausePCR has high sensitivity and specificity values in detecting SARS-CoV-2.Methods: This was a descriptive analytical study. The samples were taken from medical records of COVID-19 patients in Ulin General Hospital Banjarmasin from March to October 2020. Statistical Package for the Social Sciences (SPSS) 16.0 software and Chi-Square test were used for data analysis.Results: From 751 COVID-19 patients, 408 patients (54.32%) had rapid antibody with positive PCR, 132 patients (17.57%) had reactive rapid antibody with negative PCR, 152 patients (20.23%) had non-reactive rapid antibody with positive PCR, and 59 patients (7.85%) had non-reactive rapid antibody with negative PCR. The rapid antibody had sensitivity of 72.85% and specificity of 30.89%. From Chi-Square test, reactive rapid antibody was not correlated with PCR positive results; values of p = 0.320, odds ratio (OR) 1.20.Conclusion: The rapid test antibody could not be recommended as a diagnostic tool. In this study, it was also found that there was no relationship between reactive rapid test results and positive SARS-CoV PCR.